(3QMdI GdfGUQi GdUZQis - (3CHh YHO Gddg eMeO Hf YHO GdSdGe GdOQYj GdfGUQj,J (B1239 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efjQ GdYRe GdJcMjd GdYjfjf HeTGgOg eTGgO GdMQejf CeG HYO abO GdTQhY HYO ESJNGQI Gdehdi GdcQje hGdJYQV dfaNGJg heG YGjfJg HJdc GdCeUGQ s
(3BNQgG (B:s
(3QH YdJ Ch UaGg hJbOSJ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs